IDENTIFIKASI JEJAK KARBON SKALA RUMAH TANGGA SEBAGAI UPAYA MENGATASI PERUBAHAN IKLIM - Dedi Rosadi; Randhi Saily; Zaiyar Zaiyar; Ulfa Jusi (Universitas Trisakti, 2022)
The high level of population density in RT 002 / RW 009 Labuh Baru Timur Village, Payung Sekaki District, Pekanbaru City has the potential to be a contributor to CO2 carbon dioxide emissions. The resulting carbon emissions are from electrical energy and food consumption. The formulation of the problem of this research is how the value of the carbon footprint resulting from the consumption of food and electricity energy. The purpose of this study is to determine the value of carbon emissions. Based on the data obtained, the value of emissions from the electricity sector is 1061.106786 (kg CO2)/day, the food consumption sector is 526.33299 (kg CO2)/day. The highest emission value produced by the electricity sector from the 32nd respondent was 18.39823 (kg C02)/day, and the food consumption sector from the 48th respondent was 13.55319 (kg C02)/day.